On nonlinear dynamics behavior and control of a new model of a magnetically levitated vibrating system, excited by an unbalanced DC motor of limited power supply - Arbex, Hassan Costa [UNESP]; Balthazar, José Manoel [UNESP]; Pontes Júnior, Bento Rodrigues de [UNESP]; Brasil, Reyolando Manoel Lopes Rebello da Fonseca; Felix, Jorge Luis Palacios; Tusset, Angelo Marcelo; Bueno, Atila Madureira [UNESP] (Springer Nature, 2014)
We analyze new results on a magnetically levitated body (a block including a magnet whose bottom pole is set in such a way as to repel the upper pole of a magnetic base) excited by a non-ideal energy source (an unbalanced electric motor of limited power supply). These new results are related to the jump phenomena and increase of power required of such sources near resonance are manifestations of a non-ideal system and they are referred as the Sommerfeld effect, which emulates an energy sink. In this work, we also discuss control strategies to be applied to this system, in resonance conditions, in order to decrease its vibration amplitude and avoiding this apparent energy sink.
Keywords: Magnetically levitated body; Non-ideal energy source; Sommerfeld effect; Passive control; Active control